2016
DOI: 10.1080/21655979.2016.1197683
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of AgNPs/CS composite films: AgNPs immobilized in chitosan matrix contributes a higher inhibition rate to cell proliferation

Abstract: In this study, the cytotoxicity of sliver nanoparticle-doped chitosan composite films (AgNPs/CS) was investigated in vitro. In this slow-release system, the doped silver nanoparticles (AgNPs) might modify both the surface properties of the matrix and the ion environment of the surrounding fluid via slow-release, determining the dominant mechanism is of interest. Here, AgNPs (average size is 25 nm) were doped into chitosan (CS) films by mechanical mixing to form a slow-release system. The surface properties and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Tyliszczak et al stated that chitosan-based hydrogels modi ed with SNPs produced by sodium borohydride in concentrations of 25, 50, 75 and 100 (wt%), showed no toxic effect on dermis cells BJ (CRL-2522TM) [9]. Wang et al reported that silver immobilized in the sliver nanoparticle-doped chitosan composite lms, shows a signi cant in uence on the cell adhesion and subsequent proliferation of human umbilical vein endothelial cells [11]. Jena et al reported that chitosan-coated silver nanoparticles, using chitosan as stabilizing and reducing agent, showed no signi cant cytotoxic or DNA damage on the macrophages at the bactericidal dose [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tyliszczak et al stated that chitosan-based hydrogels modi ed with SNPs produced by sodium borohydride in concentrations of 25, 50, 75 and 100 (wt%), showed no toxic effect on dermis cells BJ (CRL-2522TM) [9]. Wang et al reported that silver immobilized in the sliver nanoparticle-doped chitosan composite lms, shows a signi cant in uence on the cell adhesion and subsequent proliferation of human umbilical vein endothelial cells [11]. Jena et al reported that chitosan-coated silver nanoparticles, using chitosan as stabilizing and reducing agent, showed no signi cant cytotoxic or DNA damage on the macrophages at the bactericidal dose [13].…”
Section: Discussionmentioning
confidence: 99%
“…Various size of the nanoparticles, different types of cell lines affect the cytotoxicity. Accordingly, some reports showed the cytotoxicity, and anti-cancer effects of silver-chitosan nanocomposite on human umbilical artery endothelial cells (HUAECs) and A549 cells (Lung cancer cell line), respectively [10,11]. In contrast, some publications advocated the non-toxicity of the chitosan-coated silver nanoparticles on healthy dermis cells (ATCC CRL-2522TM), and macrophages [9,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Δεν υπάρχουν παρόμοιες μελέτες σε μεσοθηλιακά κύτταρα που να εξετάζουν τις επιδράσεις των AgNPs στις δύο αυτές κυτταρικές λειτουργίες, με τις οποίες θα μπορούσαμε να συγκρίνουμε τα αποτελέσματα της παρούσας διατριβής. Σε αντίθεση με τα δικά μας ευρήματα, τα AgNPs έχει αποδειχθεί ότι αναστέλλουν την προσκόλληση και τον πολλαπλασιασμό των ανθρώπινων ενδοθηλιακών κυττάρων ομφαλικής φλέβας[121]. Υπάρχει, ωστόσο, μια θεμελιώδης διαφορά μεταξύ των δύο μελετών, καθώς τα ενδοθηλιακά κύτταρα αφέθηκαν να προσκολληθούν σε φιλμ χιτοζάνης AgNPs με μεταβλητό πάχος ενώ στην παρούσα διατριβή αφέθηκαν να προσκολληθούν σε υπόστρωμα φιμπρονεκτίνης.…”
unclassified